A Review on Existing Techniques for Generating Automatic Test Case for Object Oriented Software (Trinity Journal of Management, IT & Media (TJMITM), 2015)
An inevitable part of software testing entails the generation of test cases.  A good test case should have the quality to cover every aspect of test  objective. An effective and efficient test case generation is the most chal lenging and time consuming task in software testing. A good test case  characteristics to cover more given set of path coverage with reducing  time and cost of software development. Researcher have proposed dif ferent techniques to generate test case automatically. However , those  techniques also have some drawbacks. To overcome these drawbacks,  we introduce a technique (i.e. GA) to generate small numbers of efficient  test cases with expectations to cover more given set of target. In this pa per we introduce that Genetic Algorithm is quite useful search method  or technique to generate large volume of test cases very effectively and  efficiently with multiple domain.
Keywords: Automatic test case generation; classification with pros and cons; Genet ic Algorithm, MATLAB